Preparation of hydrophobic polymer using phenol resins and nylon 6 by blending for the dielectric property. (2021) - Thiruvengadam, V.; Shanmugam, V.; Vivekanand, P.A.
Abstract: Polymer blending has been widely used methodology for the preparation of a new type of high-performance polymer. Polymer blends have attracted considerable scientific and industrial interest. Preparation of hydrophobic polymer using phenol resin and nylon 6 by solution blending for the dielectric property application is described in this paper. The prepared phenol-resin nylon 6 blend structure is established by FT-IR, XRD. The thermal stability is determined by DSC-TGA. The polymer blend has a decomposition temperature of about 400 °C and exhibits good thermal stability. The water contact angle measurement shows the prepared blend has hydrophobic nature. The hydrophobic nature increases consistent with the increased concentration of phenol resin in nylon 6. This thermally stable and hydrophobic polymer blend could be used as potential material for the electrical device application.